Soft, Thiol‐ene/Acrylate‐Based Electrode Array for Long‐Term Recording of Intracranial EEG Signals with Improved Biocompatibility in Mice. Issue 5 (10th October 2021) - Fedor, Flóra Zsófia; Madarász, Miklós; Zátonyi, Anita; Szabó, Ágnes; Lőrincz, Tibor; Danda, Vindhya; Spurgin, Lisa; Manz, Connie; Rózsa, Balázs; Fekete, Zoltán
Abstract: Thiol‐ene/acrylate, a softening polymer material, rapidly gained attention during the past few years as a substrate of intracortical probes, as soft polymers can mitigate foreign body response by reducing mechanical mismatch between the neural implant and the surrounding brain tissue. This paper presents a comprehensive analysis of a thiol‐ene/acrylate based microECoG (micro – electrocorticography, μECoG) device with 31 sputtered iridium oxide electrodes. Long‐term electrochemical measurements provide firm evidence on the reliability of the novel layer structure and the related packaging method. In vivo impedance measurements indicated stable electrode yield (over 75%), without apparent signs of delamination or material degradation over 75 days. Awake recordings of theta oscillations with signal‐to‐noise ratio between 1.04 and 5.74 over this extended period also confirmed the applicability of the device. Chronic immune response characterized by Glial Fibrillary Acidic Protein staining of astrocytes and fluorescent Nissl (NeuroTrace) staining of neurons revealed only modest foreign body reaction after 80 days of implantation. The study presents novel data that confirms the feasibility of softening polymer‐based μECoG devices as chronically implantable neural interfaces. Abstract : Thiol‐ene/ as substrate material of intracortical neural probes is found to mitigate foreign body response by reducing mechanical mismatch between neural implant and brain tissue. This 10‐week‐long in vivo study is the first that confirms the electrical stability and biocompatibility of softening polymer‐based intracranial electroencephalographic device as chronically implantable neural interface.